Laporan Kasus: Henoch Schonlein Purpura pada Anak Laki-Laki 3 Tahun dengan Akut Abdomen - Edmundo Caesario Dwiputra; Laili Indah Kusumawati Noor (Majority, 2020)
Henoch Schonlein Purpura is a clinical syndrome caused by vasculitis which is most common in children. Annual HSP incidence reaches 10-20 per 100,000. Henoch Schonlein Purpura can affect all ages, but 50% of cases occur at less than 5 years of age and 75% of cases occur at less than 10 years of age. The diagnosis of HSP is based on clinical symptoms. If 2 of the 4 criteria are found, namely ≤20 years of age on pain, palpable nontrombocytopenia purpura, diffuse acute abdominal pain that gains weight after eating, and biopsy showing granulocytes in the walls of the arterioles or venules. Gastrointestinal manifestations of Henoch Schonlein Purpura occur in 60-65% of patients. The core explanation regarding the pathophysiology of gastrointestinal disorders in HSP is the deposition of immune complexes in the blood vessels of the gastrointestinal organs. In this case, the patient is suspected of having intussusception, this is in accordance with the literature which states that intussusception in 2-6% of cases can be a complication of gastrointestinal tract vasculitis in HSP. Most HSP can recover without treatment. In mild circumstances, supportive management is given in the form of hydration, nutrition, and symptomatic drug administration. The controversy of corticosteroid therapy is mainly related to the exact time of administration. At present, corticosteroids have been widely used to treat HSP with gastrointestinal and kidney manifestations.